ANALYSIS OF PARENT-CHILD INTERNET ADDICTION TEST IN SDIT AL IMAN BINTARA - Tissa Maharani (Asosiasi Dosen Muda Indonesia, 2024)
The development of information and communication technology and the implementation of distance learning during the COVID-19 pandemic have made everyone use gadgets, including children and toddlers. In addition to having a positive impact, of course, there are many negative impacts, one of which is gadget addiction. Gadget addiction can be detected using the PARENT-CHILD INTERNET ADDICTION TEST (PCIAT) developed by Dr. Kimberly Young based on Internet Addiction Test (IAT). The purpose of this research is to detect and analyze the use of gadgets and the internet using PCIAT in SDIT Al Iman Bintara students through respondent, namely their parents, and increase the awareness of parents about the dangers of gadget and internet addiction. The results of this research are, from 516 students, as many as 472 student guardians filled out the PCIAT questionnaire. A total of 288 respondent children (67.4%) showed NO SYMPTOMS of gadget addiction, 124 respondent children (29%) showed MILD symptoms, and 15 respondent children (3.5%) showed moderate symptoms. Cooperation between parents and the school is needed in regulating the use of children's gadgets, and consistency in the implementation of the rules.